Identification of Dermatophyta Fungi in the Armpits of Stroke Patients in Kandeman Subdistrict, Batang Regency - Dela Stieka Apresia; Tuti Suparyati (INDOGENIUS, 2026)
Background & Objective: Skin fungus caused by Dermatopyta is called dermatophytosis. The causative fungi are Tricopyton, Microsporum, and Epidermophyton. Dermatophyta is a group of fungi that attach to keratinous tissue, such as the stratum corneum of the skin, nails, and human hair. These fungi can cause damage to living cells by activating the immune system. Stroke patients have difficulty fulfilling their daily needs, such as maintaining personal hygiene, which increases their risk of infection with Dermatophyta sp. fungi. This study aims to identify dermatophyte fungi in stroke patients in Kandeman subdistrict, Batang regency. Method: This study used a descriptive design with a sample of 17 stroke patients in Kandeman subdistrict, Batang regency. Dermatophyte fungi were examined using a media culture method. Result: The examination results showed that all samples were negative for Dermatophyta fungi. The factors supporting these negative results were that most patients still practiced good personal hygiene, such as showering twice a day, ensuring their bodies were completely dry, maintaining excessive dryness, and not experiencing itching on their bodies. This prevented the growth of Dermatophyta fungi in the armpits. Conclusion: In conclusion, there was no Dermatophyta sp. fungal infection among stroke patients in Kandeman Subdistrict, Batang Regency.